1992
DOI: 10.1007/bf00705276
|View full text |Cite
|
Sign up to set email alerts
|

No relationship between the cell surface hydrophobicity of coagulase-negative staphylococci and their ability to adhere onto fluorinated poly(ethylene-propylene)

Abstract: The cell surface hydrophobicity of 14 encapsulated and 21 non-encapsulated coagulasenegative staphylococci (CN staph) as determined with the salt aggregation test (SAT) as well as with the xylene-water method ranged widely. Non-encapsulated strains adhered well onto fluorinated poly(ethylene-propylene) (FEP), irrespective of the hydrophobicity of the cell surface. The ability of the encapsulated strains to adhere onto FEP differed also considerably, but no correlation between the number of adherent bacteria an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It is surprising that the adhesion of S.aureus and S.epidermidis slightly changed with°s v in the range of 26.9 and 63.1 erg cm ¡2 and that both bacteria showed approximately the same adhesion percentage at the end of 24 h cultivation period. In another study, Brokke et al found no correlation between the number of adherent S.epidermidis and cell surface hydrophobicity on uorinated poly(ethylenepropylene) surfaces [20]. Recently, Gottenbos et al investigated the initial adhesion of S.epidermidis and P.aeruginase on different biomedical polymers [21].…”
Section: Resultsmentioning
confidence: 97%
“…It is surprising that the adhesion of S.aureus and S.epidermidis slightly changed with°s v in the range of 26.9 and 63.1 erg cm ¡2 and that both bacteria showed approximately the same adhesion percentage at the end of 24 h cultivation period. In another study, Brokke et al found no correlation between the number of adherent S.epidermidis and cell surface hydrophobicity on uorinated poly(ethylenepropylene) surfaces [20]. Recently, Gottenbos et al investigated the initial adhesion of S.epidermidis and P.aeruginase on different biomedical polymers [21].…”
Section: Resultsmentioning
confidence: 97%